MEDAN MAKNA DALAM SURAH AN-NAHL - R.S., Tasya Syafira; Desaalma, Angelita; Nursyalsabil, Rangga; Sampurno, Tri Anggara Medhi; Taufiqiah, Wafi (Prosiding Konferensi Nasional Bahasa Arab, 2024)
This article aims to observe, examine and explain (1) The concept of semantic field (2) What themes are discussed in Surah An-Nahl (3) What vocabulary exists within the scope of these themes. Surah An-Nahl is part of the Islamic holy scripture that contains profound messages about various aspects of human life. This analysis is conducted by elaborating the textual meanings and tracing the philosophical, moral, and practical implications of each verse in Surah An-Nahl. From analyzing Surah An-Nahl, the researcher identified 13 themes that include interconnected vocabulary within each theme. It is hoped that this in-depth analysis of Surah An-Nahl will provide a broader understanding and insight into the values contained within it.يهدف هذا البحث إلى ملاحظة وفحص وشرح (١) مفهوم الحقل الدلالي (٢) الموضوعات التي تمت مناقشتها في سورة النحل (٣) المفردات الموجودة ضمن نطاق هذه الموضوعات. سورة النحل هي جزء من الكتاب المقدس للمسلمين الذي يحتوي على رسائل عميقة حول جوانب مختلفة من حياة الإنسان. يتم إجراء هذا التحليل من خلال توضيح المعاني النصية وتتبع الآثار الفلسفية والأخلاقية والعملية لكل آية في سورة النحل. من خلال تحليل سورة النحل، توصل الباحث إلى ١٣ موضوعاً تتضمن مفردات مترابطة في كل موضوع. ومن المأمول أن يوفر هذا التحليل المتعمق لسورة النحل فهماً أوسع والقيم المتضمنة فيها.